Comparison of water use efficiency and biomass production in 10-year-old Populus sibirica and Ulmus pumila plantations in Lun soum, Mongolia - Sungsik Cho; Byambadorj Ser-Oddamba; Nyam-Osor Batkhuu; Hyun Seok Kim (Forest Science and Technology, 2019)
Although afforestation is one of the best solutions for combating desertification, it requires intensive management. To minimize management efforts in plantations in arid area, it is crucial to select suitable tree species, i.e. those with a high adaptability to xeric environments. In this study, we investigated key tree traits related to drought adaptation in Populus sibirica Hort. ex Tausch and Ulmus pumila L., planted in the Korea-Mongolia Green Belt Plantation in Lun soum, Mongolia. We found that U. pumila had a smaller leaf size and smaller specific leaf area (SLA) than P. sibirica. In addition, the water use efficiency (WUE) of U. pumila (carbon isotope-based) was significantly higher than that of P. sibirica. Although biomass production was ∼2.5 times higher in P. sibirica than in U. pumila due to the differences in leaf area, there were no statistically significant differences in the photosynthetic characteristics on an area basis. These results indicate that U. pumila has a higher adaptive potential to dry conditions than P. sibirica due to its small leaf size, low SLA, and high WUE.